Empowerment of Posyandu Cadres Through Training in Anthropometric Measurement and Assessment of Children's Nutritional Status in the Baolan Community Health Center Work Area, Tolitoli Regency - Saman, Saman; Evie, Sova; Kurniawan, Rahmat; Putri, Novica Ariyanti; Suswinarto, Dwi Yogyo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Indonesia faces a critical challenge in tackling stunting, with the country ranking third in Southeast Asia for its prevalence. From 2005 to 2017, the average stunting rate for toddlers was 36.4%, which slightly decreased to 30.8% by 2018. However, as of 2023, Central Sulawesi continues to report a high stunting prevalence of 27.2%. This growth issue severely impacts cognitive development and academic performance, leading to delayed motor skills and reduced IQ. A survey from the Tolitoli Regency Health Office indicated significant nutritional problems, particularly in the Baolan Community Health Center's jurisdiction. Despite efforts to address malnutrition, no formal training on anthropometric measurements and stunting prevention was provided to Posyandu (Integrated Health Post) cadres. This study aims to empower these cadres by providing them with training on anthropometric measurements and assessing children's nutritional status using the WHO standard Z-Score method. This community service initiative involves lectures, demonstrations, and hands-on practice for health cadres, with the goal of improving their skills in child nutritional status assessment, ultimately contributing to the national effort to reduce stunting.